Kodular-Based Arabic Learning Media for Islamic Junior High Schools: Development and Learning Outcome Evaluation - Wahyu Maulana Masnur; Maswani Maswani; Muhammad Faizurrahman (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: The limited availability of interactive digital Arabic language learning media that align with the curriculum in Islamic Junior High Schools currently represents one of the main obstacles in optimizing student engagement and learning outcomes. Research Objectives: This study aims to develop and evaluate the effectiveness of a Kodular-based Arabic learning media named HiArab in improving the learning outcomes of seventh-grade students at Islamic Junior High Schools. Methodology: This study employed a Research and Development (R&D) by the ADDIE model. Data were collected through expert validation sheets, pre-test and post-test assessments, questionnaires, observations, and documentation. The sample consisted of 26 seventh-grade students at MTsN 2 Ponorogo selected through purposive sampling. Results: The findings indicate that the developed learning media is highly feasible and effective. Expert validation results showed an average feasibility score of 89.5%, categorized as highly feasible. The effectiveness test revealed a significant improvement in students’ learning outcomes, with the average score increasing from 57.32 on the pre-test to 83.57 on the post-test. The N-Gain score of 0.61 falls within the medium-to-high improvement category, indicating a substantial learning gain. In addition, student responses to the media were very positive, with an average score of 86%, reflecting increased motivation, engagement, and ease of understanding Arabic vocabulary and pronunciation. Unique Contribution: This study contributes to Arabic language education by empirically demonstrating the effectiveness of mobile platforms and presenting a practical model for curriculum-based, interactive digital media in Islamic Junior High Schools. Conclusion: The development of HiArab proved to be highly engaging and significantly improved student learning outcomes, underscoring the transformative potential of strategic digital integration in pedagogy. Recommendations: Future research is recommended to extend its application across varied grade levels and subject areas, thereby strengthening digital innovation in Islamic education.